Poluição de microplásticos em igarapés urbanos do município de Itapiranga (AM) - Pereira, George Gustavo Libório (Brasil, 2024)
Plastics are widely used in industry and are part of the daily lives of billions of people. However, a large part of the plastics produced are discarded irregularly, which results in the contamination of ecosystems. These materials can degrade into smaller particles known as microplastics (MPs). MPs can be classified into primary and secondary, presenting different shapes, colors and sizes. These particles can be found in water and in the sediments of freshwater environments, such as lakes, rivers and reservoirs. The objective of this work was to analyze the presence of microplastics in streams (Caracaraí and Piegas), located in the urban area of the municipality of Itapiranga, Amazonas. Surface water and sediment samples were collected during the dry and flood periods. The results obtained revealed the presence of microplastics in urban streams during dry and flood periods, surface water and sediment samples showed contamination by microplastics, with a predominance of size between 1 and 5 mm, and with dark blue and red colors. Microplastics were categorized into fibers and fragments, with fibers being the most abundant. The concentrations of microplastics in the water did not directly correlate with those in the sediment, indicating the influence of hydrodynamic factors. Data related to the detection and displacement of microplastics in streams in the Amazon region are relevant for further investigations into possible environmental effects that these contaminants can have on aquatic ecosystems.